Die vakfilosofie (Deel II): Die aard van die vakfilosofie - Veldsman, T. H. (Koers, 1984)
Subject Philosophy is limited to the presuppositions of a discipline. The objective of this article is to discuss the concept "presupposition". The following aspects are covered: the nature of a presupposition; types of presuppositions; the similarities and differences among the types of presuppositions; and the relationship among the types of presuppositions. The Implications of the above discussion for the Subject Philosophy are indicated, amongst others, for the relationship between Philosophy and Subject Philosophy.